2014
DOI: 10.1002/pbc.25169
|View full text |Cite
|
Sign up to set email alerts
|

The graft‐versus‐neuroblastoma effect of allogeneic hematopoietic stem cell transplantation, a review of clinical and experimental evidence and a perspective on mechanisms

Abstract: Despite aggressive treatment, patients with high-risk neuroblastoma face high relapse rates and bleak prognoses. Increasing evidence that neuroblastoma cells are or can become immunogenic has stimulated research into novel therapies based on triggering or enhancing tumor immunity. Here we review clinical and experimental studies on this subject, the underlying immune mechanisms and perspectives for clinical application. Allogeneic hematopoietic stem cell transplantation has proven to be of substantial benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…In other instance, haplo-identical stem cell transplantations consisting of alloreactive NK cells and allogeneic NK cells adoptive immunotherapy has proven effective in the treatment of AML [5]. These confirm and support the fact that NK cells are involved and play important roles in immune response against AML.…”
supporting
confidence: 56%
“…In other instance, haplo-identical stem cell transplantations consisting of alloreactive NK cells and allogeneic NK cells adoptive immunotherapy has proven effective in the treatment of AML [5]. These confirm and support the fact that NK cells are involved and play important roles in immune response against AML.…”
supporting
confidence: 56%
“…Although autologous HSCT remains to be the mainstay of therapy for upfront treatment in high-risk neuroblastoma based on results in the 1990s, [4] allogeneic HSCT has gained limited but increasing interest in the treatment of relapsed/refractory disease supported by the proven efficacy in hematologic malignancies and selected solid tumors. [5,6] We hereby describe the first successful report of treating post-haploidentical HSCT neuroblastoma relapse with donor lymphocyte infusion (DLI) alone, thus supporting the efficacy of graft versus tumor (GvT) effect in allogeneic HSCT for neuroblastoma treatment.…”
Section: Introductionmentioning
confidence: 80%
“…In mismatched SCT, NK-mediated GvL effects reduced the relapse rates in patients with leukemia. 10,25,26 We previously showed that haplo-SCT was associated with low incidence of GvHD and TRM in patients with rHR-NB. 13 However, the 5-year EFS of 19% indicated insufficient graft-versus-tumor effects.…”
Section: Discussionmentioning
confidence: 99%